Broad [CII] line wings as tracer of molecular and multi-phase outflows in infrared bright galaxies - Janssen, A; Christopher, N; Sturm, E; Veilleux, S; Contursi, A; Gonzalez-Alfonso, E; Fischer, J; Davies, R; Verma, A; Gracia-Carpio, J; Genzel, R; Lutz, D; et al. (American Astronomical Society, 2016)
We report a tentative correlation between the outflow characteristics derived from OH absorption at 119 μm and [C ii] emission at 158 μm in a sample of 22 local and bright ultraluminous infrared galaxies (ULIRGs). For this sample, we investigate whether [C ii] broad wings are a good tracer of molecular outflows, and how the two tracers are connected. Fourteen objects in our sample have a broad wing component as traced by [C ii], and all of these also show OH119 absorption indicative of an outflow (in one case an inflow). The other eight cases, where no broad [C ii] component was found, are predominantly objects with no OH outflow or a low-velocity (≤100 km s−1) OH outflow. The FWHM of the broad [C ii] component shows a trend with the OH119 blueshifted velocity, although with significant scatter. Moreover, and despite large uncertainties, the outflow masses derived from OH and broad [C ii] show a 1:1 relation. The main conclusion is therefore that broad [C ii] wings can be used to trace molecular outflows. This may be particularly relevant at high redshift, where the usual tracers of molecular gas (like low-J CO lines) become hard to observe. Additionally, observations of blueshifted Na i D λλ 5890, 5896 absorption are available for 10 of our sources. Outflow velocities of Na i D show a trend with OH velocity and broad [C ii] FWHM. These observations suggest that the atomic and molecular gas phases of the outflow are connected.